IMPOLITENESS STRATEGIES USED BY NETIZENS IN COMMENTS COLUMN OF NISSA SABYAN INSTAGRAM ACCOUNT - Kiki Andriani; Feriyanti Elina Gultom (Universitas Negeri Medan, 2023)
This study aimed at identifying the types of impoliteness strategies based on Jonathan Culpeper theory, and how is the used of impoliteness strategies posted by the netizen. This study was conducted by applying descriptive qualitative method. The source of the data were taken from comments column posted by netizens of Nissa Sabyan Instagram Account. The technique for analyzing the data is qualitative research. The results of this research showed that there are four impoliteness are used, which are Bald on Record, Positive Impoliteness, Negative Impoliteness, and Sarcasm/Mock Politeness. There were 50 comments. In total there are 6 comments on Bald on Record (12%), 20 comments on Positive Impoliteness (40%), 18 comments on Negative Impoliteness (36%) and 6 comments on Sarcasm/Mock Politeness (12%). Based on the comments that have been analyzed, The researcher concluded that how is the used of Impoliteness Strategies, First, the writer found that the netizens mostly used positive impoliteness and negative impoliteness strategies to express their negative attitude on giving online comments of Nissa Sabyan Instagram Account. The reason could be, that in comparison to other strategies, these have a large number of sub-strategies that support positive and negative impoliteness strategies, such as ignore, uncaring, seek disagreement, scorn, ridicule the other, frighten, and so on.